A novel three-dimensional stromal-based model for in vitro chemotherapy sensitivity testing of leukemia cells. Issue 2 (February 2014) - Aljitawi, Omar S.; Li, Dandan; Xiao, Yinghua; Zhang, Da; Ramachandran, Karthik; Stehno-Bittel, Lisa; Van Veldhuizen, Peter; Lin, Tara L.; Kambhampati, Suman; Garimella, Rama
Abstract The disparate response of leukemia cells to chemotherapy in vivo, compared to in vitro, is partly related to the interaction of leukemic cells and the three-dimensional bone marrow stromal microenvironment. We investigated the effects of chemotherapy agents on leukemic cell lines co-cultured with human bone marrow mesenchymal stem cells (hu-BM-MSCs) in a three-dimensional model (3D). Comparison was made to leukemic cells treated in suspension, or grown on a hu-BM-MSC monolayer (2D conditions). We demonstrated that leukemic cells cultured in 3D were more resistant to drug-induced apoptosis compared to cells cultured in 2D or in suspension. We also demonstrated significant differences in leukemic cell response to chemotherapy using different leukemic cell lines cultured in 3D. We suggest that the differential responses to chemotherapy in 3D may be related to the expression of N-cadherin in the co-culture system. This unique model provides an opportunity to study leukemic cell responses to chemotherapy in 3D.